Accuracy of Surgeon Diagnosis in Predicting Carpal Tunnel Syndrome. (March 2021) - D'Auria, Jennifer L.; Montanez, Anthony; Toirac, Alexander; Goitz, Robert J.; Fowler, John R.
Background: The utility of electrodiagnostic studies (EDX) continues to be a point of debate in the diagnosis of carpal tunnel syndrome (CTS). If surgeons can predict the results of EDX with high accuracy, it may suggest that ordering the test is unnecessary from a diagnostic standpoint.Methods: Two surgeons with subspecialty training in hand surgery were asked to classify hands into "definitely having or not having CTS" or into an "unclear category" when presented with patients having a chief complaint of hand paresthesias. Clinical diagnosis was compared against EDX, ordered after the initial patient visit, as the reference standard.Results: Of the 175 hands, 111 hands were predicted to have CTS, 37 hands were predicted not to have CTS, and 27 hands had an unclear diagnosis. Overall surgeon accuracy was 86% (124/148). Accuracy was improved when subdivided by a positive prediction of CTS (88%) compared with a negative prediction of CTS (70%) ( P = .03). Sensitivity was 90% and specificity was 67%. The senior surgeon had a higher accuracy at 90% than the more junior surgeon at 74% ( P = .02).Conclusions: Surgeons with sub-specialty training in hand surgery are able to accurately diagnose CTS without EDX. Surgeon experience is important and resulted in a higher accuracy in predicting EDX results.